1994
DOI: 10.1038/ki.1994.63
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin system in neonatal rats: Induction of a renal abnormality in response to ACE inhibition or angiotensin II antagonism

Abstract: In experiments designed to analyze cardiovascular structure in response to antihypertensive therapy with an ACE inhibitor, we decided to start very early in life with the aim to prevent blood pressure increases and the development of vascular structural changes. In these treated groups of rats we unexpectedly observed that after they were weaned, their water consumption and urine volume, respectively, increased substantially. The present study was designed to determine if inhibition of the renin-angiotensin sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
129
0
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(145 citation statements)
references
References 15 publications
12
129
0
4
Order By: Relevance
“…It has previously been reported that mice completely lacking ACE develop renal lesions that involve blunting of the renal papilla and associated dilatation of the renal calyces (17). These lesions are almost certainly due to lack of angiotensin II production since they also occur in mice that lack angiotensinogen and in rats treated neonatally with AT 1 receptor antagonists (23,24,26). It is not clear whether the renal abnormalities are due directly to a requirement for angiotensin II in normal renal development, or if they are secondary to the low blood pressure or increased urine flow present in these animals.…”
Section: Discussionmentioning
confidence: 86%
“…It has previously been reported that mice completely lacking ACE develop renal lesions that involve blunting of the renal papilla and associated dilatation of the renal calyces (17). These lesions are almost certainly due to lack of angiotensin II production since they also occur in mice that lack angiotensinogen and in rats treated neonatally with AT 1 receptor antagonists (23,24,26). It is not clear whether the renal abnormalities are due directly to a requirement for angiotensin II in normal renal development, or if they are secondary to the low blood pressure or increased urine flow present in these animals.…”
Section: Discussionmentioning
confidence: 86%
“…Neonatal rats treated with an angiotensin-converting enzyme inhibitor presented persistent and irreversible histopathological renal abnormalities in adult life (37). These abnormalities mainly consisted of cortical tubulointerstitial inflammation, various degrees of papillary atrophy and pelvic dilation.…”
Section: Renal Development In Offspring Of Mothers That Received Angimentioning
confidence: 99%
“…The role of the RAS in altered renal development has received considerable attention. Angiotensin II is known to be important in normal renal development (109,110), and variations in dietary protein can alter the RAS (111). In the rat low-protein model, we have shown that renal tissue renin protein and mRNA, AT1R protein and mRNA, and angiotensin II levels are reduced in the newborn and young offspring compared with controls (16,19,97).…”
Section: Targets Of Programming In the Fetusmentioning
confidence: 99%